Designing a Short-Term Healthcare Service-Learning Mission Trip for Impact and Sustainability. Issue 3 (July 2021) - Adam, Jamie; Greene, Elisa
Abstract : ABSTRACT: Educators creating healthcare service-learning mission trips for students recognize that success is measured in benefit to students, the community served, and in sustainability. Partnering in Guatemala with a nonprofit ministry, Belmont University faculty describe their experience with service-learning trips and how impact was measured, particularly on students' faith and service. Useful steps for overcoming barriers to sustainability for the university and local community served are provided.